Definitive local therapy to head and neck squamous cell carcinoma with distant metastasis. Issue 3 (6th May 2022) - Borson, Steven; Shuai, Yongli; Branstetter, Barton F.; Nilsen, Marci Lee; Hughes, Marion A.; Fenton, Moon; Kubik, Mark; Sridharan, Shaum; Clump, David A.; Skinner, Heath D.; Johnson, Jonas T.; Chiosea, Simion I.; et al.
Abstract: Objectives: Data on the efficacy of including definitive local therapy to the primary site for head and neck squamous cell carcinoma (HNSCC) patients with synchronous distant metastasis are lacking. In multiple different solid tumor types, there has been benefit when using systemic therapy followed by local consolidative therapy (stereotactic ablative radiotherapy or surgery) directed at metastases. We proposed to retrospectively evaluate patients at our institution that received definitive treatment to the primary. Methods: Single institution retrospective study evaluating 40 patients with metastatic HNSCC treated with definitive surgery (55%) or chemoradiation (45%) to the primary site from 2000 to 2020. The major endpoints were overall survival (OS) and progression‐free survival (PFS) for the total population and multiple sub‐groups. Some variables were evaluated with multiple covariates Cox model. Results: The median PFS was 8.6 months (95% CI, 6.4–11.6), and OS was 14.2 months (95% CI, 10.9–27.5). In 28% of patients that received induction therapy, there was a twofold increase in median overall survival to 27.5 months. In the 33% of patients that received anti‐PD‐1 mAb as part of their treatment course, the median OS was significantly increased to 41.7 months (95% CI, 8.7‐NR) versus 12.1 months (95% CI, 8.4–14.4) with a 5‐year OS of 39%. Multivariate analysis for OS showed significance for age at diagnosis, use of IO, and number of metastatic sites. Conclusion: We observed impressive survival outcomes in metastatic HNSCC patients treated with definitive local therapy to the primary site in addition to induction and/or immunotherapy. Further study is warranted. Level of Evidence: 3. Abstract : Data on the efficacy of including definitive local therapy to the primary site for HNSCC patients with synchronous distant metastasis are lacking. We show with a single institution retrospective study that survival outcomes in metastatic HNSCC patients treated with definitive local therapy to the primary are improved.